THE INFLUENCE OF LECTURER INSTRUCTIONAL COMMUNICATION, ACADEMIC SERVICE QUALITY, AND HIGHER EDUCATION REPUTATION ON STUDENT STUDY INTEREST - Molyanti .; Sunarto . (Institut Pendidikan Tapanuli Selatan, 2021)
The aim of this study is to determine the impact of teachers' communication, academic quality and higher educational reputation on student interests. By collecting data through surveys, the method uses a quantitative approach. The research instrument used a questionnaire tested for validity and reliability using the Cronbach's alpha technique. The sample consisted of 168 people comprised of 30 male and 138 female students of the 2020 class State Polytechnicof Ujung Pandang. The research method uses multiple linear regression analysis. The study results are as follows: (1) Lecturer education communications have a positive impact of 34.1 percent on student participation in college. (2) Academic services quality has a positive impact of 26.7% upon the interest of the students in college. (3) Higher education reputation has a positive effect on student interest of 35.5%. (4) Professors' instructional communications and academic services quality have a positive impact on college students interest by 35.3%. (5) The qualities of academic services and the reputation of institutions of higher education have an effect of 40.3 percent on student interest. (6) The students' interest in study positively affects educational communication from lecturers and reputation in universities by 43.9%. (7) The student interest in studying positively influences 43.9% on teacher education communications, academic quality and the reputation of the universities.